Association between the dietary inflammatory index and risk of lung cancer: a multi-centered case-control study - Farimah Dehghani; Fatemeh Toorang; Monireh Sadat Seyyedsalehi; Bahareh Sasanfar; Hamideh Rashidian; Maryam Hadji; Alireza Ansari Moghadam; Mahdieh Bakhshi; Paolo Boffetta; Kazem Zendehdel (BMC Cancer)
Abstract Purpose Dietary factors might contribute to the risk of lung cancer by increasing the concentration of inflammatory markers. The literature-derived Dietary Inflammatory Index (DII) has been established to evaluate the inflammatory potential of diet correlated with inflammatory markers. The association between DII scores and the risk of lung cancer has been conflicting. So, in the current study, we aimed to assess the effect of pro-inflammatory dietary patterns measured with DII and the risk of lung cancer. Methods A multi-center case-control study was carried out on 616 patients with lung cancer and 3412 healthy controls. Dietary intakes were collected using a 131-item food frequency questionnaire during a face-to-face interview. The DII scores including thirty-six nutrients were calculated after energy adjustments. Finally, the association between DII level and the risk of lung cancer was evaluated by performing a multi-variable regression method after adjusting for potential confounders. Results The risk of overall lung cancer, small cell, and squamous cell carcinoma was elevated in the third tertile compared to the first tertile of the DII score, (odds ratio [OR] T3 vs. T1 of overall lung cancer = 1.38 (95% confidence interval [CI] 1.08–1.77), P trend = 0.01, OR T3 vs. T1 of squamous cell lung cancer = 1.82 (95% CI 1.02–3.24), P trend = 0.04, OR T3 vs. T1 of small cell lung cancer = 1.66 (95% CI 1.08–2.54), P trend = 0.019). However, no increase was observed in the risk of adenocarcinoma by adherence to a pro-inflammatory dietary pattern. Conclusion A positive link was found between DII and the risk of overall lung cancer, small-cell, and squamous-cell lung cancer. However, there was no association between DII and the risk of lung adenocarcinoma.